2015
DOI: 10.1016/j.aqpro.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Study on Saline Water Intrusion into the Shallow Coastal Aquifers of Periyar River Basin, Kerala Using Hydrochemical and Electrical Resistivity Methods

Abstract: Seawater intrusion generally occurs when withdrawal of fresh groundwater from coastal aquifers results in declining groundwater levels, facilitating lateral and/or vertical migration of saline water causing deterioration of groundwater quality. Electrical resistivity sounding techniques and hydrochemical studies are widely used to determine the interaction between groundwater and saline water/seawater in coastal aquifers. Vertical electrical soundings were carried out at 15 locations in the midland and coastal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 7 publications
0
10
1
Order By: Relevance
“…TDS values obtained from selected sites during different seasons are included in the Appendix (Table A4). The measured TDS range (705 to 4 340 mg/L) was higher than that observed by Kumar et al (2015) (1.21 to 774 mg/L) and Sylus and Ramesh (2015) (25 to 1 800 mg/L). Higher TDS values were observed in winter and spring relative to summer and autumn.…”
Section: Total Dissolved Solids (Tds)contrasting
confidence: 60%
See 1 more Smart Citation
“…TDS values obtained from selected sites during different seasons are included in the Appendix (Table A4). The measured TDS range (705 to 4 340 mg/L) was higher than that observed by Kumar et al (2015) (1.21 to 774 mg/L) and Sylus and Ramesh (2015) (25 to 1 800 mg/L). Higher TDS values were observed in winter and spring relative to summer and autumn.…”
Section: Total Dissolved Solids (Tds)contrasting
confidence: 60%
“…Anthropogenic discharges and runoff of wastewater into water resources can result in conductivity increase, thus rendering the water unsuitable for irrigation and domestic use (Korkanç et al, 2017). Seawater intrusion into rivers in coastal lines and delta regions may also lead to changes in pH, EC, and TDS regimes (Kumar et al, 2015;Sylus and Ramesh, 2015). The EC values at the selected sites ranged between 988 and 6 340 µS/cm (see Table A4, Appendix).…”
Section: Electrical Conductivity (Ec)mentioning
confidence: 99%
“…The electrical resistivity tomography (ERT) method was successfully applied to the spatial characterization of saltwater intrusion in coastal areas [12,[17][18][19][20], but has not yet been used to map thin freshwater lenses. ERT is especially useful wherever a network of boreholes, piezometers, and direct sampling of groundwater are available [21,22]. The point measurements are useful to calibrate the ERT method that is then used to create a series of two-dimensional images of freshwater-saltwater distribution in the aquifer [19].…”
Section: Introductionmentioning
confidence: 99%
“…The fertilizers, pesticides and other chemical products used for agriculture also affect the groundwater quality (Nag and Lahiri 2012). Several authors have reported about the quality of groundwater worldwide (Batayneh et al 2014;Senthilkumar et al 2014;Kazemi and Mohammadi 2012;Kumar et al 2015;Krishna Kumar et al 2011;Nwankwoala et al 2012). The groundwater studies were carried out in Puducherry region by Public Works Department (2007), Thilagavathi et al 2012, Nathan et al 2012, CGWB 1993, Chidambaram et al 2011and Pethaperumal et al 2010.…”
Section: Introductionmentioning
confidence: 99%